2015
DOI: 10.1002/app.42449
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic device based on a PAAm hydrogel/gold nanoparticles composite

Abstract: Stimuli-resposive hydrogels, such as poly(acrylamide), are smart materials that can be loaded with gold nanoparticles to explore the localized surface plasmon resonance effect to develop an optical device. Here we used electropolymerized poly(acrylamide) hydrogel for entrapped gold nanoparticles into gel structure (composite) to prepare a plasmonic device. Sensing tests were performed; for this bovine serum albumin molecules were placed into the composite by diffusion from an aqueous solution. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Hydrogels are widely used in tissue engineering, drug delivery, and wound dressings . Recently, efforts have been made to integrate photonic functions into hydrogel materials for novel biomedical applications, including functional optical fibers for light delivery and monitoring of blood oxygenation levels in biological tissues, cell‐containing hydrogel implants for toxicity sensing and optogenetic therapy, and nanoparticle‐embedded hydrogels for detection of biochemical analytes . However, due to the weak and brittle nature of common synthetic hydrogels, these hydrogel photonic devices are relatively fragile against external stress and strain.…”
mentioning
confidence: 99%
“…Hydrogels are widely used in tissue engineering, drug delivery, and wound dressings . Recently, efforts have been made to integrate photonic functions into hydrogel materials for novel biomedical applications, including functional optical fibers for light delivery and monitoring of blood oxygenation levels in biological tissues, cell‐containing hydrogel implants for toxicity sensing and optogenetic therapy, and nanoparticle‐embedded hydrogels for detection of biochemical analytes . However, due to the weak and brittle nature of common synthetic hydrogels, these hydrogel photonic devices are relatively fragile against external stress and strain.…”
mentioning
confidence: 99%
“…It is known that the wavelength of maximum adsorption of Au particles is affected by several parameters, including particle size and shape and the surrounding environment of gold nanoparticles . For stable colloidal dispersions of Au nanoparticles, it was observed that the wavelength of maximum absorption is red-shifted on increasing the particle size. , However, when Au nanoparticles are embedded/adsorbed/incubated in a solid matrix (polymers and inorganic supports), the extinction peak is also affected by the interactions with the solid support as well as by particle aggregation; as an example, it depends on the local refractive index; specifically, an increase of the refractive index causes a red shift of the extinction peak. At the same time, particle aggregation causes a shift to the longer wavelength region compared to single AuNPs. In light of this, the differences in the position of the absorption maximum observed in the above samples could be due to the metal nanoparticle–solid support interactions, which, in turn, could be affected by the different phosphorus species observed between ZPGly_R2-80 and ZPGly_R2-120.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have developed hydrogel optical fibers with increased flexibility, lower propagation loss, a longer function period, and a more controllable degradation rate [ 50 , 85 , 87 ]. These fibers can be used widely as drug and cell carriers [ 88 ], glucose and blood oxygenation level sensors [ 46 , 85 , 89 ], and light delivery, introducing optogenetics therapies, minimally invasive surgery, and photomedicine [ 45 , 46 , 62 , 90 ] one step closer to clinical practice.…”
Section: The Materials Of Polymer Optical Fibermentioning
confidence: 99%